The archaeology of the medieval English monarchy - Steane, John (Routledge, 1999)
Many aspects of medieval monarchy can only be recovered through archaeology. This archaeological survey of kingship in the period from the reign of William the Conqueror to that of Henry VIII brings together the physical evidence for the Kings and their courts in the form of a great variety of objects and buildings. John Steane looks at the changing perceptions of the cult of medieval kingship through symbols of power and regalia including crowns, seals and thrones, such as the Coronation Chair of Edward I. The result is a synthesis of current knowledge of the physical remains of medieval kingship that has not previously been attempted. Restoring many details of the lives and deaths of the great and powerful monarchs of the Middle Ages, this book reveals past public splendors as well as more private insights.